2012
DOI: 10.5505/tjb.2012.76486
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of asymmetric dimethylarginine and its clinical significance

Abstract: ÖZETAsimetrik dimetilarjinin nitrik oksit sentaz enziminin endojen inhibitörüdür. Nitrik oksit endotel bağımlı vazodilatasyon, damar duvarındaki düz kas proliferasyonu, hücre-hücre etkileşimleri, platelet adezyon ve agregasyonunun inhibisyonu ile monosit adezyonu inhibisyonu gibi düzenleyici fonksiyonlara sahiptir. Arjinin amino asitinin modifiye bir formu olan asimetrik dimetilarjinin, metilenmiş proteinlerin proteolizi sonucu oluşur. Hücrede oluşan ve salınan net asimetrik dimetilarjinin miktarı, arjinin met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…In contrast to ADMA levels, arginine and citrulline levels were sig- indicated that connection of protein degradation degree with the formation of ADMA is not known and ADMA is not the only factor in the pathogenesis of cardiovascular disease, probably the interactions of protein methylation, DDAH, ADMA and NO pathways are contributed to pathogenesis [11].…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…In contrast to ADMA levels, arginine and citrulline levels were sig- indicated that connection of protein degradation degree with the formation of ADMA is not known and ADMA is not the only factor in the pathogenesis of cardiovascular disease, probably the interactions of protein methylation, DDAH, ADMA and NO pathways are contributed to pathogenesis [11].…”
Section: Resultsmentioning
confidence: 96%
“…Increased levels of ADMA accompanied by cardiovascular risk factors such as hypertension, smoking, diabetes mellitus, dyslipidemia, insulin resistance and lead to vascular injury and increase the atherosclerosis have been reported [11,22]. BD is a systemic inflammatory vasculitis with unknown etiology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some limitations to our study. In addition to the limited number of participants, several publications in the literature suggest that a few metabolic disorders, insulin resistance, glucose tolerance, diabetes mellitus, hyperlipidemia, chronic kidney disease, hypertension, and coronary heart diseases may be associated with increased ADMA levels (61,62). Moreover, in this study, we found that total cholesterol and triglyceride levels in OCD patients were higher compared to those in the control group, but there was no difference between the groups in terms of blood glucose, urea, and creatinine levels.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main reasons and consequence of endothelial dysfunction is impaired nitric oxide (NO) bioavailability [6]. NO bioavailability is mostly regulated by the activity of nitric oxide synthase (NOS, EC.1.14.13.39).…”
Section: Introductionmentioning
confidence: 99%